PENGARUH PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH PADA MATERI REAKSI REDUKSI OKSIDASI TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA DI KELAS X SMA NEGERI 1 SAMBAS - Ririn Arista; Mawardi Mawardi; Rizmahardian Azhari Kurniawan (Jurnal Ilmiah Ar-Razi, 2017)
ABSTRACTOne of the ways to improve student’slearning activity and learning outcomes using studentcentered learning model. Therefore, this study applied cooperative learning model make amatchtype and analyzed its impact on student’s learning activity and learning outcome. This study was Quasi Experimental Research using Nonequivalent Control Group Design. The samples were selected by using purposive sampling technique, which are XD as the experiment class and XG as the control class. Data was collectedusing measurement, observation, and direct communication techniques. Learning outcome test, observation sheets and interview guidelines were used as data collection tools. Based on the data analysis which uses non-parametric U-Mann Whitney showed that there were differences in students learning activity and learning outcome between experiment class and control class. The Effect sizethat was obtained for student’s learning activities and learning outcomes were 1.17 and 0.86, respectively. Both are in high category of influence, which influenced amounted to 36.65% of the student’s learning activity and 30.52% of the student’slearning outcome. This study shows that cooperative learning model make a match has a major effect toward student’s learning activity and learning outcome.Keywords: Learning Activity, learning outcomes, make a match, reduction-oxidation